The development of novel approach for risk quantification in coal procurement - Ibrahim J.A.; Hashim A.H.; Majid M.; Mat Tahar R. (2023)
Determining the optimum level of security is an area where more research is required. In principle, the optimum level of security that a system provides is determined by the interaction between cost of providing extra security and value to consumers. Risks in energy system have to be quantified in order to identify the level of security. To make comparison between cost of providing energy security and level of security, the quantified risks have to be in similar common variable as the costs. Then, an optimum level of security and cost can be estimated using appropriate methods. The objective of this paper is to present the development of Non-delivery Probability Table (NdPT) for use in coal procurements in energy system. This table will provide the probabilities of non-delivery for every supplier involved in supplying fuel for the system. These probabilities then can be used to quantify the risks in energy systems. 2010 IEEE.